Choosing The Right Performance Rating Method: A Comparative Review of Performance Rating Methods in Time Study - Aida Husna Ahmad,; Haziq Asyraaf Abu Bakar,; Mohd Faris Afiq Mohd Azhar,; Saliza Azlina Osman,; Tay Sin Kiat,; Shahrul Azmir Osman, (International Journal of Integrated Engineering, 2026)
Time study is a widely used work measurement technique in industrial engineering, providing a systematic approach to determine standard times for task completion. Central to this process is performance rating, which is a critical adjustment mechanism that converts observed work time to a standard performance level, directly impacting the fairness and accuracy of established time standards. Despite decades of industrial application, performance rating remains contentious due to inherent subjectivity and significant inter-observer variability, yet limited comparative research exists to guide practitioners in method selection. This paper addresses this gap by presenting a systematic comparative review of 4 principal performance rating methods, which are speed rating, the Westinghouse system, synthetic rating, and objective rating. Through critical analysis of their operational mechanisms, contextual applicability, and practical limitations, this review reveals that method selection should be strategically aligned with task characteristics, operational complexity, and resource availability rather than pursuing a universal approach. The findings provide guidance for industrial engineers and operations managers to optimize performance rating accuracy through informed method selection and appropriate implementation strategies, with proper training and calibration identified as essential enablers of reliable results across all methods.